A comparison of independent police complaint bodies: interview data, 2022-2024 - Johansen, Anja (UK Data Service, 2025)
The handling of citizens' complaints against the police across national and jurisdictional boundaries is difficult to compare as available data are generally incompatible or absent. Independent police complaints bodies (IPCBs) are highly vulnerable to criticism of being costly and ineffective. The aim of this comparative project was to provide the data needed for contextualisation of IPCBs through long-term, in-depth comparison of the functioning of IPCBs in the UK, Canada, France, Germany, and Japan. The findings can be used to contextualise IPCBs in other countries. The methodologies behind the data collection were designed to match the data available for the five countries, to recommend common principles for data collection, and to best highlight similarities and dissimilarities in the handling of citizens’ complaints by IPCBs in all five countries. Quantitative data were gleaned from IPCB annual reports. Due to highly dissimilar methodologies for data collection and definitions of categories, an important outcome of the project was to identify information that needed to be collected for some IPCBs, and recommend consistent formats for data collection. The UK the data cover three types, gleaned from the Independent Office for Police Complaints for England/Wales (IOPC), the Scottish Police Investigation and Review Commissioner (PIRC), and the Police Ombudsman for Northern Ireland (PONI). First, transcripts of 22 interviews (out of a total of 27) conducted with IPBC practitioners, police, and criminal justice personnel involved with investigating, assessing, and sanctioning complaints against police officers. These interviews were conducted between September 2022 and April 2024. Secondly, two reports were produced based on anonymised summaries of discussions from two stakeholder events, reflecting experiences, concerns, and suggestions for improvement of police complaints handling. Finally, included visualisations of the institutional set-up of the IPCB, PIRC and PONI, to illustrate the range and diversity of arrangements for UK IPCBs. Against the backdrop of increased powers and resources granted to police agencies for combating terrorism and other newly perceived threats in many mature democracies, the POLACS project compares levels of empowerment for citizens through accountability mechanisms (independent external oversight bodies, police complaints procedures and similar schemes). Additional police powers, technologies and transnational police networks add to the already far-reaching powers that police agencies have, granting the police new and powerful ways of monitoring and interfering in citizens' lives and thus their fundamental rights. Yet, it has often proven to be very difficult to get the reform of police complaints procedures onto the political agenda. Today, with audio-video recording equipment becoming ubiquitous and with encounters between police and members of the public disseminated instantly via the internet, the issue has moved from the fringes to the mainstream as a live political issue. Researchers from Canada, France, Germany, Japan and the UK have been cooperating in the POLACS project. In the light of persistent public concerns in many democratic countries about effective police accountability, particularly in cases of death or serious injury to members of the public, there is an urgent need to improve the empirical basis for comparison of external independent police accountability schemes and to develop international standards for 'good practice'. The project has also explored the accountability structures for transnational policing within institutional frameworks, such as Interpol or the European Union's Area of Freedom, Security and Justice, as well as in transnational police networks. For transnational policing, mostly situated outside national parliamentary oversight and access to justice, accountability can be perceived as particularly deficient. The academic investigators involved in the POLACS project, with their theoretical and empirical expertise on police accountability, have been revising and adapting current accountability theories and standards to the empirical reality that has been rapidly developing since the 1990s. Comparison has been adopted as the most effective methodological approach for contextualising performance of national and sub-national schemes and a necessary basis for developing international standards for 'good practice'. Policy-makers, practitioners and activists involved in reforming external police accountability mechanisms face great difficulties in contextualising current or proposed schemes with other schemes, past and present, as the available qualitative insights and quantitative data are often not comparable. Only by bringing existing data and knowledge together will it be possible to contextualise national and sub-national police accountability schemes and identify what data and insights are missing.